KEBERHASILAN PROGRAM HUTAN KEMASYARAKATAN DALAM MELESTARIKAN HUTAN - Ritonga, Wilson Mandela; Rochana, Erna (SOCIOLOGIE, 2013)
This study aims to identify and explain the Community Forestry Program in the Forest Preserve and explain the impact of the program on the community forestry living around the forest, the method used is qualitative research, informants in this study were three people from the community forestry and 2 people from the forest service. Data were collected by way of interviews with community forestry that participated in the activities of Community Forestry Program. The research was conducted in the village district Tribudisyukur source victorious western province of Lampung Lampung regency. Data analysis techniques in the study through three stages, namely data reduction, Stage Presentation of Data and Conclusions Phase. Research results indicate that the Community Forestry Program has managed to preserve the welfare of society and the forest, which can be viewed at the focus of this research is successful in approximately Welfare Forest (economic, employment, daily necessities), Success in Community Participation for preserve and rehabilitate forests (Planning Phase Rehabilitation, Rehabilitation Implementation, Maintenance and Development of forests), and success in securing forest disturbance illegal logging, forest encroachment, poaching of wildlife, forest fires and wildlife disorders.Keywords: Community forestry program, forest preserve